challenge of implementing the European network of protected areas Natura 2000 - Kati, Vassiliki; Hovardas, Tasos; Dieterich, Martin; Ibisch, Pierre L; Mihok, Barbara; Selva, Nuria (Conservation biology, 2015)
Established under the European Union (EU) Birds and Habitats Directives, Natura 2000 is one of the largest international networks of protected areas. With the spatial designation of sites by the EU member states almost finalized, the biggest challenge still lying ahead is the appropriate management of the sites. To evaluate the cross‐scale functioning of Natura 2000 implementation, we analyzed 242 questionnaires completed by conservation scientists involved in the implementation of Natura 2000 in 24 EU member states. Respondents identified 7 key drivers of the quality of Natura 2000 implementation. Ordered in decreasing evaluation score, these drivers included: network design, use of external resources, legal frame, scientific input, procedural frame, social input, and national or local policy. Overall, conservation scientists were moderately satisfied with the implementation of Natura 2000. Tree modeling revealed that poor application of results of environmental impact assessments (EIA) was considered a major constraint. The main strengths of the network included the substantial increase of scientific knowledge of the sites, the contribution of nongovernmental organizations, the adequate network design in terms of area and representativeness, and the adequacy of the EU legal frame. The main weaknesses of Natura 2000 were the lack of political will from local and national governments toward effective implementation; the negative attitude of local stakeholders; the lack of background knowledge of local stakeholders, which prevented well‐informed policy decisions; and the understaffing of Natura 2000 management authorities. Top suggestions to improve Natura 2000 implementation were increase public awareness, provide environmental education to local communities, involve high‐quality conservation experts, strengthen quality control of EIA studies, and establish a specific Natura 2000 fund.